Evaluation of Online Learning Processes in FKIP Universitas Lampung During Covid-19 Pandemic - Mudrikah, Achmad; Saefuloh, Nandang Arif; Gintings, Abdorrakhman (FKIP Universitas Lampung, 2020)
This research intends to reveal the increasing of senior high school students' mathematical understanding and mathematical disposition. The study involved 124 students from ordinary private schools and Islamic boarding private school. The research method used was quasi-experiment pretest and posttest control group design. The research goals are to examine students’ mathematical understanding ability and mathematical dispositions based on the type of school, type of learning, and students' prior mathematical abilities. The results showed that mathematical understanding and mathematical dispositions of students who received problem-based learning assisted by mathematics kit (PBL-MK) was better than students who only received PBL. Islamic boarding schools students can show better mathematical understanding when studying with PBL-MK. Islamic boarding school students who have high and medium prior mathematical abilities gain better mathematical understanding than non-boarding school students. Keywords: problem-based learning, mathematics kit, mathematical understanding, mathematical disposition. DOI: http://dx.doi.org/10.23960/jpmipa/v21i2.pp109-119